1984
DOI: 10.3382/ps.0631115
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vitamin Deficiency and Level of Dietary Protein on the Incidence of Leg Problems in Broiler Chicks

Abstract: Diets containing either 22 or 30% protein were supplemented with a vitamin mix where one of 11 added vitamins were singly eliminated from the mix. Male, day-old broilers were fed these diets to 3 weeks of age, and weight gains, feed utilization, and leg problems were recorded. In general, the higher protein diet did not result in a greater incidence of leg problems; however, it did alter performance of several of the vitamin-deficient diets as compared to the lower protein diet. Of the 11 vitamins studied only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…However, Hester et al (1985) showed that lowering the lysine and methionine plus cystine content of diets to 90% of those recommended by the NRC did not result in a signi cant reduction in the incidence of leg abnormalities. Summers et al (1984) showed that chicks fed on a higher protein diet did not show a greater incidence of leg problems.…”
Section: Introductionmentioning
confidence: 96%
“…However, Hester et al (1985) showed that lowering the lysine and methionine plus cystine content of diets to 90% of those recommended by the NRC did not result in a signi cant reduction in the incidence of leg abnormalities. Summers et al (1984) showed that chicks fed on a higher protein diet did not show a greater incidence of leg problems.…”
Section: Introductionmentioning
confidence: 96%
“…Not all studies have shown that lower protein diets decreased the incidence of leg deformities. Summers et al (1984) reported the effect of a 22 vs 30% protein diet fed from 0 to 3 weeks of age on leg problems of male broiler chicks. Although the incidence of deformed legs and mobility did not respond to the two diets in the same manner between the two experiments, Summers et al (1984) concluded that chicks fed the higher protein diet did not show a greater incidence of leg problems.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, it is reported that the LP diets resulted in a decrease in the BW of the birds (Hurwitz et al, 1998;Yalçın et al, 1998;Faria Filho et al, 2005). Dietary protein level had no significant effect on GS as Summers et al (1984) found. Likewise, Hester et al (1985) showed that lowering the amino acid such as the lysine and methionine 1 cystine content of diets to 90% from NRC recommendation did not cause a significant reduction in the incidence of leg abnormalities.…”
Section: Discussionmentioning
confidence: 77%